P.131 Does a multidisciplinary triage pathway facilitate better outcomes after spine surgery?. (5th June 2019) - Wu, A; Fourney, D; Liu, L
Abstract : Background: The Saskatchewan Spine Pathway (SSP) facilitates timelier imaging and more appropriate surgical referrals. In this prospective study, pre- and post-operative wait times, satisfaction, and outcomes were compared between SSP and conventionally referred surgical patients.Methods: A prospective matched cohort comparison of 150 patients (SSP group n=75; conventional group n=75) undergoing elective lumbar surgery for mechanical back and leg pain between 2011 and 2016 was performed with 1 year follow-up. Outcomes were measured with patient questionnaires, Oswestry disability index (ODI), visual analogue back and leg pain scores (VAS), and EuroQol Group 5 –Dimension self-report (EQ5D).Results: Baseline measures were the same in both groups. Wait times to see the surgeon and for surgery were the same, and wait time for MRI was significantly shorter for the SSP group (p<0.001). SSP patients utilized more non-operative treatment strategies such as physiotherapy (p<0.04), and had higher satisfaction with pre-surgical care (p=0.03). Good surgical outcomes were obtained in both groups with no significant differences.Conclusions: There are minimal differences in post-surgical outcomes for SSP patients versus conventionally referred patients; however, the SSP facilitates significantly shorter wait times for MRI and non-operative treatment strategies. Pre-surgical patient satisfaction is significantly higher among SSP patients.